The Study of Relationship Between Social Participation and Quality of Life of Old People Who Are Member of Senior Association of Tehran City in 2011 - Shirzad Moradi; Hossein Fekrazad; Mir Taher Mousavi; Maliheh Arshi (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: Purpose of this study was to analyze the relationship between Social Participation and its dimensions (Institutional & Non-Institutional Involvements) on elderly`s quality of lif in those who are members of Senior Association in Tehran. Methods & Materials: Research was as descriptive-analytical and sectional design. Statistical Society of Research has included all elderly who were the members of senior association of Tehran city and are more than 60 years of age. Two-hundred (200) elderly from senior associations of Districts 1, 12 & 20 by simple random and cluster sampling were selsected. Research tools included were: Lypad Quality of Life Questioner, Social Participation questioner prepared by the researcher, and demographic information check list executed among the sample society. Information achieved was separately analyzed by Cronbach's Alpha Coefficient, Pearson Correlation Coefficient, Linear Regression, K-S, F & T Methods. Results: Comparison of Quality of Life Average Score (P≥0.05) and Social Participation (P≥0.05) among the old men and women showed non-significant statistical difference, also correlation coefficient of “social participation” and “life quality” (r=0.778) showed a meaningful relationship between such variables. Also it was determined that 63 percent (R=0.63) of variance difference of life quality should be foreseen by the model of this research by using the regression. Conclusion: The results of the research showed a meaningful relationship between “social participation” and its dimensions with quality of life of elderly. This implied that non institutional involvements were more common among aforementioned elderly.